2023
DOI: 10.1038/s41598-023-35407-x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' preferences in therapeutic decision-making in digestive oncology: a single centre cross-sectional observational study

Pierre Nizet,
Charlotte Grivel,
Pauline Rabeau
et al.

Abstract: Considering the preferences in Shared Decision Making (SDM) of patients with Digestive Cancer (DC) is crucial to ensure the quality of care. To date, there is limited information on preferences in SDM of patients with DC. The objectives of this study were to describe digestive cancer patients’ preference for involvement in therapeutic decision-making and to identify variables associated with these preferences. An observational prospective study in a French university cancer center has been conducted. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…For example, vanLieshout et al ( 2021) cited earlier noted that the motivation to reduce uncertainty, and the motivation to maximize positive information represent separate and independent drives. Nizet et al (2023), also cited earlier, found that individual preferences constituted motivation for information-seeking in the context of patient decision-making. Stoffel et al (2022) compared the effect of different temporal frames on informationseeking behaviour when the participants were presented with information on the incidence of colorectal cancer (CRC).…”
Section: Motivational Theoriesmentioning
confidence: 56%
See 2 more Smart Citations
“…For example, vanLieshout et al ( 2021) cited earlier noted that the motivation to reduce uncertainty, and the motivation to maximize positive information represent separate and independent drives. Nizet et al (2023), also cited earlier, found that individual preferences constituted motivation for information-seeking in the context of patient decision-making. Stoffel et al (2022) compared the effect of different temporal frames on informationseeking behaviour when the participants were presented with information on the incidence of colorectal cancer (CRC).…”
Section: Motivational Theoriesmentioning
confidence: 56%
“…However, the reference lists of the thirty-two papers in the second set were checked and only four citations to information science literature on information-seeking were found. These were: Case and Given (2016) cited by Criado-Perez et al (2023); Case, et al (2005) cited by Restrepo-Castro, et al (2023), Madge (2023) cited by Nizet et al (2023), andWilson (2000) cited by Aguirre, et al (2022).…”
Section: Discussion and Overall Conclusionmentioning
confidence: 99%
See 1 more Smart Citation